CONVENTIONAL THERAPIES FOR PSORIASIS - A. Rebora (PAGEPress Publications, 2011)
Conventional treatments of psoriasis include topical and systemic drugs. For sake of brevity, the presentation will deal only with systemic therapy. Three drugs are presently available in Italy: methotrexate, acitretin and cyclosporin A. Their efficacy is almost identical, all of them achieving PASI 75 in about 60% of cases in 12 weeks The indications (which, in Italy, do not include psoriasis for methotrexate), the contraindications, the interactions, the adverse effects and the precautions in their use will be discussed. Methotrexate side effects account for more than 10% of cases and include nausea and vomiting and chiefly increase of blood levels of liver enzymes. Acitretin side effects are numerous and varied, the most severe being increase of liver enzymes and blood lipids, renal impairment, and teratogenicity. Cyclosporin side effects are chiefly hypertension and renal failure. The Author concludes that cylosporin is the drug with the best efficacy/side effect ratio, though it should be used in selected cases. Key words: Psoriasis, methotrexate, cyclosporine A, acitretin